Development and validation of a scale to measure students’ feelings about school: An exploratory and confirmatory factor analysis approach - Serra, Lídia; Alves, José Matias; Pinheiro, Generosa (American Journal of Education and Learning, 2025)
Over the past fifty years, schools have undergone significant changes in terms of technology and digitalization, as well as pedagogical, organizational, social, and cultural shifts, which have led to transformations in relationships between students and teachers, peers, and within the broader school environment. Dynamic contexts impose new challenges to teaching and learning, and emotions, feelings, and moods play a central role in this process. Understanding students’ relationships with the school can provide valuable insights into their engagement, well-being, and academic success. However, this problem remains under-evaluated in school practice due to the lack of simple tools that can capture students’ emotional experiences in a regular and contextualized manner. This study aims to address this gap by developing a scale to evaluate middle and high school students’ interactions with peers and teachers, perceptions of school climate, teaching and learning, and assessment. The study used a 31-item questionnaire, and a survey was conducted with students aged 10 to 19 years old. An exploratory factor analysis (N = 200) and a confirmatory factor analysis (N = 300) were performed to identify and validate a hypothetical construct that explains the observed variables. Then, using an exploratory design to examine the preliminary structure and psychometric properties of the Exploratory Students’ School Experience Scale (ESSES), the study reached two models. While one model exhibited good fit, the other model reflected a balance between statistical adequacy and conceptual parsimony, aiming to retain a structure that is both interpretable and psychometrically sound.